Pain intensity and physical performance among individuals with fibromyalgia in mid-to-late life: The influence of depressive symptoms. (June 2022) - Serpas, Dylan G; Zettel-Watson, Laura; Cherry, Barbara J
This study investigated the mediating role of depressive symptoms among 147 middle-aged and older adults with FM in the relationship between pain intensity and 4 objective measures of physical performance: Fullerton Advanced Balance scale (FAB), 6-Minute Walk Test (6MWT), 30-Second Chair Stand (30SCS), and 8-Foot Up and Go Test (8FUPGT). Asymptotic mediation analyses revealed that depressive symptoms fully mediated the relationship between pain intensity and FAB (95% CI [−0.40, −0.10]) and 8FUPGT (CI [0.02, 0.11]) and partially mediated the relationship to 6MWT (CI [−9.15, −2.20]) and 30SCS (CI [−0.29, −0.06]). Findings support the evaluation of co-morbid depression in FM.